[Scrapbook of portraits of actors, singers, vaudeville artists and musicians] (1900)
Portraits have been cut from theatre programmes and newspapers. Some of the companies named: George Musgrove's New Opera Company, J.C. Williamson, J. & N. Tait.
Keywords: Theater -- Australia; Scrapbooks -- Australia